A survey on DoS/DDoS mitigation techniques in SDNs: Classification, comparison, solutions, testing tools and datasets. (April 2022) - Alhijawi, Bushra; Almajali, Sufyan; Elgala, Hany; Bany Salameh, Haythem; Ayyash, Moussa
Abstract: Software-Defined Networking (SDN) is a modern network approach that replaces the conventional network architecture with a flexible architecture by separating the control plane from the data plane. SDN simplifies network management and monitoring through logically centralized intelligence, programmability, and abstraction. SDN architectures are vulnerable to attacks, such as the Denial of Service (DoS) attack. This article reviews and classifies the research efforts on SDN and DoS. We categorized the research efforts into two groups: solutions to cope with DoS attacks on SDN and SDN-based solutions to tackle DoS attacks on networks. The first group of solutions includes six categories: Table-Entry, Scheduling, Architectural, Flow Statistics, Machine Learning, and Hybrid solutions. Furthermore, the article surveys the tools and datasets considered by the reviewed contributions. The article presents a detailed comparison among reviewed approaches in terms of network devices, network layers involved, DoS attack's types, and targets of attacks. Graphical abstract: Highlights: Software-Defined Networking architectures are vulnerable to Denial-of-Service attacks. A review on solutions to cope with Denial-of-Service attacks on Software-Defined Networking. A review on Software-Defined Networking based solutions to tackle Denial-of-Service attacks. About 72.9% of the solutions used control layer modules. The article surveys the tools and datasets considered by the reviewed contributions.